PO 18162 - Clinical and functional outcomes of tibiotarsal arthrodesis in foot drop treatment - Christovan Ribeiro, Evandro Junior; Dutra Ernesto Junior, Gunther Geraldo; Damião Prata, Sérgio; Rizzo, Marco Antônio (Scientific Journal of the Foot & Ankle, 2019)
Objective: To evaluate the clinical and functional outcomes of the treatment of foot drop with joint degeneration through tibiotarsal arthrodesis. Methods: Nine patients with foot drop were retrospectively evaluated, including 2 with lumbar disc disease, 4 with sequelae of poliomyelitis, and 3 with peroneal nerve injury. All patients underwent tibiotarsal arthrodesis (open surgery), and functional improvement of the limb was analyzed during the postoperative period. The mean age of the patients was 45 years and 10 months, and 6 patients were men. Results: The outcomes were evaluated using the American Orthopedic Foot and Ankle Society (AOFAS) ankle-hindfoot scale translated into and adapted to Portuguese. In the postoperative assessment, 6 patients had mild or occasional pain, and 3 patients had no pain. The mean AOFAS ankle-hindfoot score was 36 points before surgery, ranging from 26 to 39, and 73 after surgery, ranging from 42 to 91. Conclusion: Tibiotarsal arthrodesis in patients with foot drop showed satisfactory outcomes, improvement in pain and gait and, consequently, improvement in quality of life.